Manual laryngeal reposturing as a primary approach for mutational falsetto. (23rd April 2016) - Roy, Nelson; Peterson, Elizabeth A.; Pierce, Jenny L.; Smith, Marshall E.; Houtz, Daniel R.
Abstract : Objectives/Hypothesis: Mutational falsetto is a functional voice disorder characterized by failure of the male high‐pitched preadolescent voice to transition to the lower pitch of adolescence and adulthood. Few objective outcomes data exist regarding the effectiveness of voice therapy for this poorly understood disorder. This study examined the immediate effects of a single therapy session using manual laryngeal reposturing as a primary approach in the management of mutational falsetto. Study Design: Retrospective case series, pre‐/posttreatment. Methods: Manual circumlaryngeal techniques, including digital laryngeal reposturing maneuvers, were used as the primary approach to treat 12 consecutive males with mutational falsetto (mean age 17.5 yrs., range 14–25 years). Pre‐ and posttreatment audiorecordings of connected speech and sustained vowel samples were submitted to auditory‐perceptual and acoustic analysis to assess the effects of a single voice therapy session. Acoustic estimates of severity in both connected speech and sustained vowel productions were computed using the Cepstral Spectral Index of Dysphonia (CSID), a multivariate dysphonia summary tool that incorporates cepstral and spectral measures. Results: Pre‐ and posttreatment comparisons confirmed a significant change in the direction of normal vocal function within a single treatment session for both listener‐ and CSID‐based estimates of dysphonia severity. Conclusion: Behavioral therapy using manual laryngeal reposturing by an experienced voice clinician is an effective and efficient primary approach for mutational falsetto. Level of Evidence: 4. Laryngoscope, 127:645–650, 2017